Dukungan Keluarga dalam Respon Lansia Terhadap Tingkat Depresi - Muhhammad Pauzi; Vera Kurnia; Sardini Sardini (JURNAL KESEHATAN TERAPAN, 2026)
In Indonesia, most elderly people live with their families, but there are also many elderly people who end up living in nursing homes, which are shared living facilities for the elderly provided by the government. The purpose of this study was to determine the relationship between family support and depression levels among elderly people at the Sabai Nan Aluih Sicincinnursing home. This study used a descriptive correlational research design with a cross-sectional approach using a questionnaire as the research instrument. The sampling technique used total sampling with a total of 85 respondents. Bivariate data analysis was performed using the chi-square test. The results of the study obtained from 85 respondents found that 69 respondents received poor family support and 16 respondents received good family support, so that 43 respondents were found to experience moderate levels of depression. From the chi-square test results, a p-value of 0.0001 was found, which is less than 0.05, meaning that here is a relationship between family support and depression levels in the elderly. Based on this study, it can be concluded that family support plays an important role in the psychological development of the elderly. The results of this study can be used as input for nursing home health services to convey to families the importance of playing a role in the psychological development of the elderly by always visiting them at the nursing home.